How to make urban freight transport by tram successful? - Katrien De Langhe; Hilde Meersman; Christa Sys; Eddy Van de Voorde; Thierry Vanelslander (Journal of Shipping and Trade (JST), 2019)
Many national and international bodies, such as the European Commission, encourage the use of environment-friendly transport modes. Local and national authorities take more and more measures, for instance road pricing, loading/unloading spaces and low-emission zones, to prevent negative transport-related externalities in urban areas. Hence, transport and logistics operators consider alternative ways to deliver goods in urban areas by using electric vehicles, cargo bikes, inland vessels and rail transport. Which of these alternative modes is appropriate for which transport flow depends on multiple factors, including the available transport infrastructure, the goods volume, the measures taken by the authorities and the presence of congestion. This paper focuses on urban freight transport by tram and the conditions for a successful implementation. A successful implementation is defined as an implementation that is viable, i.e. the difference between the change of the costs and the change of the benefits exceeds a certain threshold value. The viability is studied from a business-economic and a socio-economic perspective for a dedicated freight tram, a freight wagon behind a passenger tram and the transport of parcels by a passenger tram. A viability model is developed, based on a social cost-benefit analysis. The working of this model is illustrated by applying it to the city of Antwerp. The main findings show that the use of a freight wagon attached to a passenger tram provides more potential than a dedicated freight tram. A courier taking the tram to deliver some parcels can be viable as well. For all three types of tram transport, the socio-economic benefits exceed the business-economic ones. Critical factors affecting the viability include the transported volume, the efficiency of the current road transport, the timing of the transport, the need for post-haulage and the operational costs of both road and rail.
Keywords: 650; City logistics; Urban freight distribution; Rail Tram; Social cost-benefit analysis